Implementasi Desain Ikonografi Khatulistiwa Park Menggunakan Digital untuk Rias Fantasi melalui Pembelajaran Project - Dea Intan Berliana; Erna Setyowati (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
The development of digital technology in vocational education encourages the use of design applications as learning media that can improve students' creativity and visual abilities. In artistic makeup learning, careful design planning is an important stage before the process of executing body painting works. This study aims to analyze the effectiveness of using Canva and CorelDRAW applications in designing iconographic designs as body painting work concepts for makeup students. The study uses a quantitative approach with a quasi-experimental design. The initial stage of the study was carried out through validation of the learning design using the expert judgment method by three experts. The results of the expert validation showed a feasibility percentage of 95.3% with a very valid category. The results showed that the validation of the instrument by three experts obtained results with a very valid category, which indicates that the instrument meets the aspects of visual aesthetics, elements and principles of art, creativity of beauty products, as well as meaning and visual representation in fantasy makeup body painting works. The results of the independent sample t-test also showed a significance value (2-tailed) of 0.013 (<0.05) which indicates a significant difference between the use of Canva and CorelDRAW applications in the design process, with the final result being that the design in CorelDraw has a higher value than the design with Canva. The integration of digital technology, a project-based learning approach, and the use of iconography based on local wisdom can support the development of creativity and artistic value in students' work.